Germline RET mutation carriers in Japanese patients with apparently sporadic medullary thyroid carcinoma: A single institution experience. Issue 5 (October 2016) - Kihara, Minoru; Miyauchi, Akira; Yoshioka, Kana; Oda, Hitomi; Nakayama, Ayako; Sasai, Hisanori; Yabuta, Tomonori; Masuoka, Hiroo; Higashiyama, Takuya; Fukushima, Mitsuhiro; Ito, Yasuhiro; Kobayashi, Kaoru; et al.
Abstract: Objective: Genetic testing for RET germline mutation can be useful to distinguish whether a patient with medullary thyroid carcinoma (MTC) is genuinely sporadic or hereditary. Conducting a routine preoperative germline RET genetic screening for all patients with MTC has the clinical benefit, i.e., avoidance of unnecessary total thyroidectomy in the selected patients. We sought to clarify the incidence of germline RET mutation carriers in Japanese patients with apparently sporadic MTC and to address the differences in clinicopathological characteristics between true sporadic MTC and hereditary MTC in these patients, all of whom were treated at Kuma Hospital. Methods: A total of 134 patients with apparently sporadic MTC who underwent surgery between 1996 and 2014 were enrolled. All patients underwent a germline RET gene mutation analysis preoperatively. Results: Germline mutations in RET proto-oncogene were identified in 20 of the 134 (14.9%) apparently sporadic MTC patients. No significant difference in clinicopathological characteristics was observed between the patients with sporadic MTC ( n = 114) and those with hereditary MTC ( n = 20) except for the RET gene carriers' younger age at diagnosis and presence of multifocal and bilateral lesions. Conclusion: Germline RET mutations were identified in 14.9% of Japanese patients with apparently sporadic MTC. No clearly decisive clinicopathological characteristics was observed to distinguish whether an apparently sporadic MTC case was genuinely sporadic or unconsciously hereditary. For the treatment strategy decision, it is advantageous to conduct a routine preoperative germline RET genetic screening for all patients with MTC, even if their MTC is apparently sporadic.